Fruit and seed biometry and seedling morphology of parkia discolor (Spruce ex Benth.) - Pereira, Sammy Aquino; Ferreira, Sidney Alberto do Nascimento (Revista Árvore, 2017)
Parkia discolor (Spruce ex Benth.) is a species of floodplain forest permanently flooded, mainly used in folk medicine and with economic potential. The purpose of this study was to estimate the biometric characteristics of fruits and seeds of Parkia discolor and describe the morphology and development of its seedlings and young plants. On average, fruits have shown the following dimensions: 18.45 cm long with pedicel, 13.25 cm long without pedicel, 4.4 cm wide and 0.66 cm thick mass of 11.91 g. The seeds have shown 1.73 cm long, 0.68 cm wide and 0.39 cm thick mass of 0.38 g. A thousand seeds mass was estimated to be 361.15 g and the number of seeds per kilogram was 2769. The fruits and seeds of these species are preyed by insects of the families Scolytidae, Nitidulidae, Cerambycidae and Bruchidae. Germination is epigeal - phanerocotylar; the seedling presents hypocotyl herbaceous, sessile cotyledons, based split, eophyll compound, paripinnatus with 1-3 pairs of leaflets, most 2 pairs, with the insertion of a spherical gland leaflets, bright green. The young plant has a woody base with 5 eophylls, alternate and presents between 21-26 pairs of foliolums. The use of plastic bags of 900 cm3was more proper than using a styrofoam tray with “cell” of 125 cm3for the development of the plants during the period of three months. © 2017, Sociedade de Investigacoes Florestais. All rights reserved.
Biometria do fruto e da semente e morfologia da plântula de Parkia discolor (Spruce ex Benth.)